2021
DOI: 10.1111/1467-8500.12512
|View full text |Cite
|
Sign up to set email alerts
|

Active representative bureaucracy, homogeneous organizational context, and deviation from official policy among street‐level bureaucrats

Abstract: Studies of representative bureaucracy have shown how minority groups are often underrepresented in public agencies. They also indicate that the match between the backgrounds of the bureaucrats and their clients has a strong effect on minority groups. Less attention has been devoted to the question of what happens when streetlevel bureaucrats (SLBs) from a minority group serve clients in organizations all of whose clients belong to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
3
1
0
Order By: Relevance
“…Second, on the individual level, the findings are in line with a large body of research indicating that street-level bureaucrats actively represent their clients by using their discretion when implementing policy (Diab & Cohen, 2021;Grissom et al, 2009;Meier, 1993;Roch et al, 2010;Selden, 1997;Sowa & Selden, 2003;Zamboni, 2020). They reinforce findings in the literature that the actions of street-level bureaucrats benefit clients with whom they share a common demographic or social identity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Second, on the individual level, the findings are in line with a large body of research indicating that street-level bureaucrats actively represent their clients by using their discretion when implementing policy (Diab & Cohen, 2021;Grissom et al, 2009;Meier, 1993;Roch et al, 2010;Selden, 1997;Sowa & Selden, 2003;Zamboni, 2020). They reinforce findings in the literature that the actions of street-level bureaucrats benefit clients with whom they share a common demographic or social identity.…”
Section: Discussionsupporting
confidence: 83%
“…Third, the findings reveal how street‐level bureaucrats see the outputs of their active representation. Like the findings of Diab & Cohen, 2021, Grissom et al, 2015, and Zamboni, 2020, my findings illustrate how the active representation of minorities both directly and indirectly leads to policy outcomes that benefit them in the street‐level public service environment. Fourth, unlike previous representative bureaucracy studies that focus on demographic characteristics of bureaucrats and clients such as ethnicity, race, and gender (Wilkins & Wenger, 2015), I focus on sexual orientation.…”
Section: Discussionsupporting
confidence: 73%
“…We demonstrate that some of our participants actively represent clients with whom they share an identity by taking actions that change the official policy. These findings accord with previous results indicating that street-level bureaucrats may act entrepreneurially when they actively represent (Davidovitz, 2022b) minority citizens by deviating from existing policies (Diab & Cohen, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…For example, Holt and Gershenson (2019) have shown that racial representation of street-level bureaucrats in North Carolina primary schools reduces the suspensions and absences of students from the represented group. A study by Diab and Cohen (2021) on Arab civics teachers in Arab schools in Israel has demonstrated how they actively represent their students by deviating from the formal curriculum. Headley and Wright II (2020) found that New Orleans police officers of color are less likely to use excessive force on civilians of color.…”
Section: Literature Reviewmentioning
confidence: 99%